Intensified ambulatory cardiology care: effects on mortality and hospitalisation—a comparative observational study - Sawicki, Olga Anastasia; Müller, Angelina; Glushan, Anastasiya; Breitkreuz, Thorben; Wicke, Felix; Karimova, Kateryna; Gerlach, Ferdinand M.; Wensing, Michel; Smetak, Norbert; Bosch, Ralph Frank; Beyer, Martin (Scientific reports, 2020)
Since 2010, an intensified ambulatory cardiology care programme has been implemented in southern Germany. To improve patient management, the structure of cardiac disease management was improved, guideline-recommended care was supported, new ambulatory medical services and a morbidity-adapted reimbursement system were set up. Our aim was to determine the effects of this programme on the mortality and hospitalisation of enrolled patients with cardiac disorders. We conducted a comparative observational study in 2015 and 2016, based on insurance claims data. Overall, 13,404 enrolled patients with chronic heart failure (CHF) and 19,537 with coronary artery disease (CAD) were compared, respectively, to 8,776 and 16,696 patients that were receiving usual ambulatory cardiology care. Compared to the control group, patients enrolled in the programme had lower mortality (Hazard Ratio: 0.84; 95% CI: 0.77-0.91) and fewer all-cause hospitalisations (Rate Ratio: 0.94; 95% CI: 0.90-0.97). CHF-related hospitalisations in patients with CHF were also reduced (Rate Ratio: 0.76; 95% CI: 0.69-0.84). CAD patients showed a similar reduction in mortality rates (Hazard Ratio: 0.81; 95% CI: 0.76-0.88) and all-cause hospitalisation (Rate Ratio: 0.94; 95% CI: 0.91-0.97), but there was no effect on CAD-related hospitalisation. We conclude that intensified ambulatory care reduced mortality and hospitalisation in cardiology patients.
Gesehen am 14.10.2020